Development of immunochromatographic assay for the on-site detection of salbutamol - Yaowapa Khamta (2018)
Salbutamol, one of the β-agonists, is misused as a growth promoter in meat producing animals. In-house synthesized colloidal gold was conjugated with the polyclonal anti-salbutamol antibodies. A rapid immunochromatographic assay was developed in a competitive format. The salbutamol-BSA conjugate and goat anti-rabbit IgG were immobilized on a nitrocellulose membrane as test and control lines, respectively. The color intensity of a purple test line was inversely proportional to the amount of salbutamol presenting in the samples. The sensitivity was estimated to be about 80ng/mL of salbutamol in PBS. The method can be useful as an on-site screening procedure for detection of salbutamol.